The real-world evidence to the effects of primary psychological healthcare system in diluting risks of suicide ideation in underrepresented children/adolescents: an observational, multi-center, population-based, and longitudinal study - Wei Li; Xuerong Liu; Qianyu Zhang; Xiaobing Tian; Xianyong An; Jidong Ren; Xiaodi Han; Jingyu Lei; Chang Shen; Yanyan Li; Ji Chen; Lei Xia; et al. (Child and Adolescent Psychiatry and Mental Health)
Abstract Background Establishing a primary psychological healthcare system to prevent suicide was eagerly advocated. Such system was developed as a low-cost healthcare framework integrating family, school, and hospitals to provide early psychological screening and intervention. However, it remains unclear whether such a policy-driven and low-cost healthcare system could be practical, especially with equal benefits for underrepresented children/adolescents. We aimed to examine the real-world practical effects of the primary psychological healthcare system in preventing suicide ideation among children/adolescents, particularly underprivileged ones. Methods The study was conducted using an observational, multi-center, population-based, and longitudinal design. A total of 19,140 children and adolescents were sampled from lower- and middle-income areas in Nanchong, western China, with the majority for being underprivileged and underrepresented. They were followed up for one year. The primary outcome was the incidence of reported severe suicide ideation after implementing the primary psychological healthcare system at the 0.5-year and 1-year follow-ups, compared to baseline. Subgroup analysis was conducted to examine the equal benefits of the system for underrepresented children/adolescents. Results The risks of suicide ideation for children/adolescents included in the system were found to be significantly lower compared to those not included at 0.5-year (adjusted relative risk [aRR] 0.28, 95%CI 0.23–0.33; p < 0.001) and 1-year follow-ups (aRR 0.28, 95% CI 0.23–0.33; p < 0.001). The effects were also observed among underrepresented children/adolescents, including “left-behind” children/adolescents, “single-parent” children/adolescents and children/adolescents in especially difficult circumstances (CEDC, all pcorrected < 0.001). The effects in “left-behind” children/adolescents, CEDC, and “single-parent” children/adolescents were found to be non-inferior to the typically developing cohort at non-inferiority thresholds of 30%, 35%, and 45%, respectively (all pcorrected < 0.05). Conclusions The primary psychological healthcare system was effective in reducing suicide ideation risks among children/adolescents over a period of at least 1 year. However, certain underprivileged groups, such as orphans and unattended children, did not experience the same level of benefits, highlighting the need for targeted improvements.